2021
DOI: 10.3389/fgene.2021.750990
|View full text |Cite
|
Sign up to set email alerts
|

Translational and Clinical Applications of Dental Stem Cell-Derived Exosomes

Abstract: Mesenchymal stem cells (MSCs) are promising seed cells in tissue repair and regeneration due to their featured properties of self-renewal and multipotency. However, a growing body of evidence has demonstrated that MSCs exert biological functions mainly through secreting exosomes. Exosomes, which contain RNA, proteins, lipids, and metabolites, are new players in regulating many fundamental processes and play important roles in regenerative medicine. Exosomes not only mimic the effects of their parent cells but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…Increasing evidence has proved that sEVs derived from MSCs could promote the regeneration of skin [ 16 , 17 ], bone [ 18 , 19 ], and cartilage [ 20 , 21 ]. In parallel, the potential clinical application of sEVs derived from dental stem cell in dental tissue regeneration has been shared [ 22 ]. DFSCs conditioned medium was able to provide a favourable microenvironment for self-renewal and osteogenesis of PDLSCs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has proved that sEVs derived from MSCs could promote the regeneration of skin [ 16 , 17 ], bone [ 18 , 19 ], and cartilage [ 20 , 21 ]. In parallel, the potential clinical application of sEVs derived from dental stem cell in dental tissue regeneration has been shared [ 22 ]. DFSCs conditioned medium was able to provide a favourable microenvironment for self-renewal and osteogenesis of PDLSCs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, an increasing number of studies have shown that exosomes play a key role in the growth, metastasis, and drug resistance of various cancer cells ( Cheng et al, 2019 ; Mai et al, 2021 ). Our study screened exosome-related lncRNAs related to prognosis and constructed a prognosis-related lncRNA risk model for liver cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…hDPSCs can also release hDPSC-EVs, including exosomes and microvesicles, into hDPSC-CM [ 35 , 62 , 74 ]. hDPSC-EVs are packed within a lipid bilayer membrane.…”
Section: Action Of Evs Released From Hdpscs (Hdpsc-evs)mentioning
confidence: 99%